Implementation of the Role of Advocates in Handling and Resolving Inheritance of Adopted Children at Lutfi S.H and Partners Advocate Office - Nadia Farhatul Musyarrofa; Mohammad Hendra; Khusnul Hitaminah; Hasan Basri (Indonesian Journal of Law and Economics Review, 2026)
General Background Inheritance disputes remain a major civil law issue because estate distribution often depends on contested interpretations of statutory heirship. Specific Background In cases involving adopted children, Indonesian civil inheritance law under the Civil Code prioritizes blood relations and surviving spouses, while adoption regulations emphasize child protection and administrative validity rather than automatic heir status. Knowledge Gap Limited empirical attention has been given to how advocates translate these legal rules into practical dispute handling at Lutfi S.H. and Partners Law Office. Aims This study examined advocates’ implementation in handling and resolving adopted child inheritance disputes and identified the legal standing of adopted children within the Indonesian civil inheritance system. Results The findings show that advocates work through consultation and case analysis, dispute-resolution strategy, and legal assistance and representation. Preventive work includes legal education and preparation of wills, adoption documents, and grants; repressive work includes negotiation, mediation, litigation, evidence organization, and courtroom representation. Adopted children are not automatic statutory heirs under Article 832 of the Civil Code but may receive estate portions through wills or grants, subject to legitieme portie. Novelty The study integrates empirical advocate practice with civil inheritance doctrine to explain preventive, educational, and solution-oriented legal services in adoption-related estate conflicts. Implications The findings support stronger legal planning, public legal awareness, and professional assistance to secure certainty, justice, and proportional protection in adopted child inheritance disputes. Highlights: Legal representatives use consultation, mediation, and courtroom assistance across conflict handling. The Civil Code prioritizes blood relatives and surviving spouses as statutory beneficiaries. Asset portions for non-biological minors depend on formal declarations or grant instruments. Keywords: Role of Advocates, Inheritance Disputes, Adopted Children, Civil Law, Inheritance.